Don't ask customers what they want, ask your staff - Kirkby, Jennifer (Henry Stewart Talks, 2009)
Are employees engaged?, Training, measuring, rewarding, Customer insight, Creating the customer value proposition, Sales through service, Co-creation at John Lewis, WOW's for Haringey council